Growth and Characterization of Pure and L-Alanine Sodium Nitrate doped Potassium Dihydrogen Phosphate Single Crystals - Loretta, Fernando; Perumal, S.; Ramalingom, S. (Asian Journal of Chemistry, 2012)
Single crystals of pure and L-alanine sodium nitrate (LASN) doped potassium dihydrogen phosphate (KDP) were grown from aqueous solution by slow evaporation technique at room temperature. The grown crystals were colourless and transparent. The grown crystals were subjected to single crystal X-ray diffraction studies and powder X-ray diffraction studies to study their structural characteristics. The functional groups present in the grown crystals were identified using FTIR spectral analysis. EDAX analysis confirms the presence of L-alanine sodium nitrate in the doped potassium dihydrogen phosphate crystal. UV-Visible transmission spectral studies and non-linear optical studies indicate that the optical transparency and second harmonic generation efficiency of potassium dihydrogen phosphate crystals are enhanced due to L-alanine sodium nitrate doping. Microhardness studies show that the L-alanine sodium nitrate doped potassium dihydrogen phosphate crystal is harder than pure potassium dihydrogen phosphate.